Special issue on Programming with Dependent Types Editorial. (2017) - SWIERSTRA, WOUTER; DYBJER, PETER
Abstract : There has been sustained interest in functional programming languages with dependent types in recent years. The foundations of dependently typed programming can be traced back to Martin–Löf's work in the 1970s. In the past decades, this vision has given rise to the development of proof assistants and functional programming languages based on dependent types. The increased popularity of systems such as Agda, Coq, Idris, and many others, reflects the growing momentum in this research area. After sending out our first call for papers in October 2015, we are happy to accept six articles in this special issue covering a wide spectrum of topics.